(untitled) (Global Journal of Management and Business Research, 2020)
Purpose: This study investigates the implementation of customer relationship management in AL Rajhi Islamic banks. The study postulates that customer relationship management has succeeded in AL Rajhibank and that Rajhi bank is adopting a customer-centric view as culture, and finally that customer relationship management enhance customer loyalty in Al Rajhibank. Design: The author developed a qualitative approach using a single case study. The data was obtained through secondary data and semi-structured interviews from Rajhi bank.